What it is like to go to war - Marlantes, Karl (New York : Atlantic Monthly Press : distributed by Publishers Group West, 2011)
In his memoir, Marlantes relates his combat experiences in Vietnam and discusses the daily contradictions warriors face in the grind of war, where each battle requires them to take life or spare life. He also underscores the need for returning veterans to be counseled properly
Keywords: Marlantes, Karl; Vietnam War, 1961-1975 -- Personal narratives, American; Veterans -- Mental health